Phenolic compositions, and antioxidant performance of olive leaf and fruit (Olea europaea L.) extracts and their structure–activity relationships. (June 2015) - Xie, Pu-jun; Huang, Li-xin; Zhang, Cai-hong; Zhang, Yao-lei
Highlights: Phenolic compositions of OLE and OFE were well identified. Antioxidant performances of OLE and OFE with different models were assessed. OLE had a stronger antioxidation than OFE except for ⋅O2 − scavenging ability. Phenolic structure–antioxidant relationships were explored in detail. OLE is a potential functional additive due to its strong antioxidation. Abstract: The compositions of olive leaf extract (OLE), bound phenolics of olive leaf (BPOL), olive fruit extract (OFE) and bound phenolics of olive fruit (BPOF) were determined by HPLC/UV–vis, and the antioxidant activity was evaluated based on the reducing power and different types of radical scavenging capacities, i.e., DPPH⋅, ⋅OH, ABTS⋅ + and O2 ⋅ − . The comparison of the structural differences in their DPPH⋅ scavenging capacity with FRAP provided insight into the phenolic structure–antioxidant activity relationships. Both OLE and OFE consisted of oleuropeosides, flavones and phenolic acids. Oleuropein was highly concentrated in OLE, where caffeic acid and luteolin were predominant in OFE. OLE exhibited a dose-dependent behavior and high antioxidant ability due to the synergism of its phenolic compounds. Conversely, OFE displayed poor reducing power and antiradical activity, but its superoxide radical scavenging capacity was stronger than that of OLE. Chlorogenic acid dominated in BPOL with an approximately 2-fold amount than that in BPOF. The antioxidant capacity mainly depended on the catechol moiety, the number of hydroxyl groups and a double bond conjugated to the 4-position on the aromatic ring. OLE may therefore be more suitable than OFE as a functional food ingredient due to its stronger antioxidant activity.